VD_FINDINFO HC / 2010 / 273 vom 1. März 2010 - VD Tribunal cantonal (2010)
VISITE, RELATIONS PERSONNELLES, OBLIGATION D'ENTRETIEN, ENFANT, PERSONNE DIVORCÉE, CARACTÈRE EXTRAORDINAIRE | 125 al. 1 CC, 273 al. 1 CC, 285 al. 1 CC, 286 al. 3 CC